A Biomonitoring Kualitas Air Sungai Kalibokor Sebrang Institut Teknologi Adhi Tama Surabaya Menggunakan Metode Biotilik: Biomonitoring Kualitas Air Sungai Kalibokor Sebrang Institut Teknologi Adhi Tama Surabaya Menggunakan Metode Biotilik - Achmad Chusnun Ni’am; Alfida Novita Sari; Kharisma Balqist Nabilah; Geovano Jorisson Terrukeni; Amirul Mukminin; Cahaya Bagus Syah (Media Ilmiah Teknik Lingkungan (MITL), 2022)
The Kalibokor drainase is a branch of the Kalimas River which passes Sukolilo District as the downstream. Sukolilo District is dominated by residential areas, educational areas, commercial areas and hospitals where some of the wastewater discharges directly to the Kalibokor drainase. The purpose of this study was to determine the watershed conditions of the mafcroinvertebrates types found using biologic method. This research is descriptive with a survey approach that identifies the biota of the Kalibokor drainase as an indicator of water pollution in Sukolilo District. Data analysis was carried out by starting with the identification of the obtained macroinvertebrates, then clasify biota become 2 groups, namely EPT (Ephemeroptera, Plecoptera, and Tricoptera) and non-EPT, then calculating the Water Pollution Index. The results showed that the Kalibokor drainase in Klampis Ngasem Village, Sukolilo District was included in the moderately polluted category.